تاريخ الأبنية الطبية في دمشق - الأبيض, شيرين (Latakia University Journal -Engineering Sciences Series, 2019)
City of Damascus represents the Syrian leading example among the global cities by its great historical role in cultural fields and science development; the content of the research clarifies the leading historical role of Damascus in medical architecture, wherein Hippocrates established the first medical buildings and schools, 800 years ago the Arab adopted the Parisian Jundishapur principles in their cities, where, Muawiya and Alwalid established first Arab medical buildings, which was indicating to the progress of medical science in Damascus at that time, through the history, Syrian doctors were ambassadors of health and science to all world`s cities; the research emphasized that, the prosperity of science must be accompanied by the flowering of the civilized buildings and structures where these sciences exercises and progressing, the research has been classified historically the ancient medical facilities in Damascus, to correspond with the importance of Damascus role as an example of the Syrian cities that were beacons of science, culture and civilization all over the world, the documentation of the history of the place and the architectural works, which contained this activity, and located it within the city, considered as a remarkable work in order to show the importance of historical Medical Buildings through the history of medical science evolution; the research was built based on historical references, researches, and documents that date the history of such facilities. تاريخ الأبنية الطبية في دمشق تمثل مدينة دمشق أنموذجاً من المدن السورية الرائدة عالمياً بدورها التاريخي الكبير في المجالات الحضارية وتطور العلوم؛ يوضح مضمون البحث الدور الريادي التاريخي لدمشق في مجال العمارة الطبية، ففيها أبقراط أنشأ أول مبانيه ومدارسه الطبية، قبل 800 سنة من مدرسة جنديسابور الفارسية التي اعتمد أسسها العرب في مدنهم، وبها أنشأ الخلفاء معاوية والوليد أول مباني طبية عربية، وهذا ما يدل على تقدم العلوم الطبية في دمشق آنذاك، وعلى مدى التاريخ كان الأطباء السوريين سفراء العافية والعلم إلى جميع مدن العالم في جميع العصور حتى الآن؛ وقد أكد البحث على أن ازدهار العلوم لابد وأن يرافقه ازدهار حضاري في الأبنية والمنشآت التي تمارس فيها هذه العلوم وتتقدم، وقد صنف البحث المنشآت التاريخية الطبية في دمشق تاريخياً لتتوافق مع أهمية ودور دمشق كنموذج للمدن السورية التي كانت منارات علم وثقافة وحضارة للعالم، إن توثيق تاريخ المكان والأعمال المعمارية التي احتوت هذا النشاط، وتحديد موقعه في المدينة، يٌعد عملاً هامهاً بهدف بيان أهمية المنشآت الطبية التاريخية إلى جانب تاريخ تطور العلوم الطبية؛ وقد بُني البحث استناداً للمراجع التاريخية والأبحاث والوثائق التي تُؤرخ لمثل هذه المنشآت.